Investigating Students’ Perceptions of Language Terms through Technology at Dehasen University - Mariska Febrianti; Azizatul Banat; Dhanu Ario Putra (Linguists : Journal Of Linguistics and Language Teaching, 2021)
The Covid-19 pandemic has made various changes in all aspects of life, such as economy, social, politics, lifestyle and education. This can be seen from the government urging the public to limit their activities and enforce self-isolation so as to encourage increased access to technology. Technology has become a very important role and is needed in the current situation because the government urges to reduce social activities. Likewise in the field of education, with the Covid-19 pandemic, all learning processes at all education levels are conducted online. This is the basis for the findings of several previous studies related to the emergence of several new terms used by the government and socialized to the public related to pandemics. From those several previous studies, the researchers saw that there was no research related to the level of public understanding of new terms that appeared during the Covid-19 pandemic. Therefore, this study aims to determine the level of student understanding of new terms that emerged during the Covid-19 pandemic. This study used a survey method for students at University of Dehasen Bengkulu using a questionnaire. From the research result, it can be concluded that most students at University of Dehasen Bengkulu, specifically Physical Education Study Program do not know the new terms. This is because many of Physical Education students are in remote areas which are very affected by the weather and electricity, so accessing information on TV and the internet often faces obstacles.